2020
DOI: 10.1177/0957650920934312
|View full text |Cite
|
Sign up to set email alerts
|

Effect of porosity gradient in cathode gas diffusion layer of polymer electrolyte membrane fuel cells on the liquid water transport using lattice Boltzmann method

Abstract: In this paper, a two-dimensional model has been developed to simulate the liquid water transport in a cathode gas diffusion layer with different porosity gradients in polymer electrolyte membrane fuel cells (PEMFCs). Due to the complexity of porous media, the simulation was carried out by lattice Boltzmann method. According to dimensionless numbers that characterize liquid water transport in porous media, simulation conditions were similar to the liquid water transfer into the gas diffusion layer of PEMFC. Dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 47 publications
0
12
0
Order By: Relevance
“…In recent years, fuel cell assemblies with a porosity gradient have received attention from many scholars. GDL with a porosity gradient can enhance the ability of GDL to remove water, the bending stiffness of GDL, and its steady-state performance. A double-layer microporous layer with a porosity gradient prepared using the double coating method was proposed by Chun et al, and the water permeability and water removal ability of GDL was enhanced. The two-dimensional liquid water transport model of cathode porosity gradient GDL was established by Habiballahi et al They found that GDL with a porosity gradient can effectively enhance the water removal ability of GDL and that the porosity of GDL near the catalytic layer should be smaller than that near the gas channel.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…In recent years, fuel cell assemblies with a porosity gradient have received attention from many scholars. GDL with a porosity gradient can enhance the ability of GDL to remove water, the bending stiffness of GDL, and its steady-state performance. A double-layer microporous layer with a porosity gradient prepared using the double coating method was proposed by Chun et al, and the water permeability and water removal ability of GDL was enhanced. The two-dimensional liquid water transport model of cathode porosity gradient GDL was established by Habiballahi et al They found that GDL with a porosity gradient can effectively enhance the water removal ability of GDL and that the porosity of GDL near the catalytic layer should be smaller than that near the gas channel.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, fuel cell assemblies with a porosity gradient have received attention from many scholars. GDL with a porosity gradient can enhance the ability of GDL to remove water, the bending stiffness of GDL, and its steady-state performance. A double-layer microporous layer with a porosity gradient prepared using the double coating method was proposed by Chun et al, and the water permeability and water removal ability of GDL was enhanced. The two-dimensional liquid water transport model of cathode porosity gradient GDL was established by Habiballahi et al They found that GDL with a porosity gradient can effectively enhance the water removal ability of GDL and that the porosity of GDL near the catalytic layer should be smaller than that near the gas channel. The multilayer GDL structure makes GDL easier to keep water in the membrane to increase ion conductivity, and the steady-state performance and voltage stability of the fuel cell are strengthened .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Many studies have been conducted on the factors affecting the dynamic water transport in the GDL. Compression under the rib, 24,[40][41][42][43][44] GDL wettability, 25,[45][46][47] structure of GDL such as porosity and pore size [48][49][50][51][52] are important parameter on water transport in GDL that is investigated in previous work.…”
Section: Introductionmentioning
confidence: 99%